Antibiotic resistance, biofilm formation, and virulence factors of isolates of staphylococcus pseudintermedius from healthy dogs and dogs with keratitis - Wang, Zhihao; Guo, Long; Li, Jun; Li, Jianji; Cui, Luying; Dong, Junsheng; Meng, Xia; Qian, Chen; Wang, Heng (Frontiers in Veterinary Science, 2022)
Staphylococcus pseudintermedius, isolated from the canine conjunctival sac, were few reported. This study focused on (a) the distribution rate of S. pseudintermedius in the canine conjunctival sac; (b) the antibiotic resistance; (c) the ability to produce biofilm; and (d) the dissemination of virulence factors in S. pseudintermedius strains. There were 35 healthy corneal dogs and 40 bacterial keratitis dogs who participated in this investigation. The S. pseudintermedius strains were screened for antibiotic resistance against 8 different molecules using Kirby-Bauer assay. The ability to produce biofilm was investigated using the microtiter plate assay (MtP) and the amplification of icaA and icaD genes. Virulence factors were evaluated. Forty dogs with bacterial keratitis and thirty-five healthy dogs have been surveyed. There were 67 and 65 aerobic bacterial isolates isolated from the 35 cornea healthy canines and 49 samples with the bacterial keratitis, respectively. S. pseudintermedius (14/67, 20.9% in healthy group and 15/65, 23.08% in keratitis group) were most frequently isolated in both groups. All the S. pseudintermedius strains had the highest percentage of susceptibility to rifampin (97%) and neomycin (97%), and the resistance to tetracycline (3%). Virulence factors such as lip (97%), hlgB (97%), and hlgA (97%) were found in most strains, and 89.66% of strains resulted in biofilm producers. In conclusion, S. pseduintermedius were the common bacterium in canine conjunctivitis sac and cornea ulceration in Yangzhou, China; the virulence factor carrying rate and biofilm formation ability were high.